Student’s Responses of Using Mobile Legends Bang Bang as A Game Based Learning Media in Teaching Vocabulary Mastery on Junior High School in Padalarang - Muhammad Akbar; Aseptiana Parmawati (IKIP PGRI Bojonegoro, 2026)
This study explores students’ responses toward the use of Mobile Legends Bang Bang (MLBB) as a Game-Based Learning (GBL) media in teaching English vocabulary mastery among eighth-grade students at a junior high school in Padalarang. The study addresses students’ difficulties in learning vocabulary through conventional methods, which often lack engagement and contextual relevance. MLBB, as a popular digital game among adolescents, was utilized to provide a more meaningful and motivating learning experience. A qualitative descriptive method was applied, and data were collected through a questionnaire consisting of open-ended and close-ended items. Thirty eighth-grade students participated in the study after experiencing vocabulary learning activities that incorporated MLBB. The questionnaire responses were analyzed to identify students’ perceptions and attitudes. The findings show that students responded positively to the use of MLBB in vocabulary learning. They stated that the game helped them understand vocabulary in context, increased their motivation, and made learning more enjoyable. Students also felt more confident and engaged during the learning process.